Effect of Astragalus injection treatment for viral myocarditis: a systematic review and meta-analysis - Dinala jialiken; Lichao Qian; Shiwu Wen; Shuai Ren; Yadong Fan; Yi xuan Dong; Chong Zou (European Journal of Medical Research)
Abstract Background Astragalus injection has been utilized in traditional Chinese medicine to treat a variety of diseases. The purpose of this systematic review was to evaluate the effectiveness of Astragalus injection in the treatment of viral myocarditis. Methods English databases such as PubMed, Cochrane Library, and EMBASE, and Chinese databases of Sino Med, China National Knowledge Infrastructure (CNKI), the VIP Information Resource Integration Service Platform, and Wanfang Data Information Site, were searched from their inception until May 1, 2024. The outcome measures of this study included the effectiveness rate, creatine kinase (CK), aspartate aminotransferase (AST), creatine kinase Isoenzyme (CK-MB), lactate dehydrogenase (LDH), cardiac troponin I (cTnI), and electrocardiogram (ECG). Results Twenty-six studies were included in this analysis, comprising a total of 2793 patients. Meta-analyses indicated that, compared to standard treatment alone, the Astragalus injection group demonstrated significant advantages, achieving an effectiveness rate of 92.79% (1094 cases). In contrast, the control group, which included 1108 cases, had an effectiveness rate of 77.71% (861 cases). Additionally, the Astragalus injection group exhibited the following benefits for patients affected by viral myocarditis: decreasing ∆AST [weighted mean difference (WMD) = − 14.23, 95% confidence interval (CI) (− 24.17, − 4.30), P < 0.05]; ∆CK [weighted mean difference (WMD) = − 34.84, 95% confidence interval (CI) (− 48.03, − 21.65), P < 0.05], lowering ∆CK-MB [WMD = − 7.64, 95% CI (− 9.30, − 5.99), P < 0.001], ∆cTnl [WMD = − 0.18, 95% CI (− 0.27, − 0.10), P < 0.001], ∆LDH [WMD = -41.93, 95% CI (− 55.97, − 27.90), P < 0.05], and ∆cTnI [WMD = − 0.18, 95% CI (− 0.28, − 0.08), P < 0.05]. Conclusion Astragalus injection may have a therapeutic effect in patients with viral myocarditis by reducing levels of AST, CK, CK-MB, LDH, and cTnI, improving ECG results, and increasing the overall effectiveness rate for those affected by this condition. Trial registration: This study registered with PROSPERO before conducting the systematic review. The registration number is CRD42021239660.